Utilization of Oyster Shells as a Substitute Part of Cement and Fine Aggregate in the Compressive Strength of Concrete - Bunyamin Bunyamin; Amir Mukhlis (Graduate Program of Syiah Kuala University, 2020)
The compressive strength of concrete depends on the physical characteristics of the concrete forming materials. Oyster shells originating from Krueng Neng, Aceh Besar are very abundant, left unattended by fishermen, causing pollution of the surrounding environment. Oyster shell dust contains CaO, which can be used as a partial substitution of cement. Therefore, it is necessary to study oyster shell ash as cement replacement and fine aggregate in concrete production. This research aims to determine the compressive strength of concrete using shell ash as cement replacement and fine aggregate. The oyster shells were obtained from Krueng Neng, Lamjamee Village, Jaya Baru, Aceh Besar District. The oyster shells were crushed with a Los Angeles Test machine and sieved with sieve size 2.36 mm for fine aggregate and sieve #200 for cement replacement. The water-cement ratios (w/c) were 0.4, 0.5 and 0.6. The results showed that concrete's compressive strength with 5% cement replacement level was higher than the concrete with cement only. Meanwhile, for other replacement levels, the compressive strengths of concrete specimens were lower than control specimens.